Чародейские каникулы: приключения - Иванов Антон (Волшебные приключения Тимки Ружина, 2003)
Экземпляры: (20071214) / Инвентарный номер: 43797 / Цена: / Сис.шифр: Р2 / Авт.знак: И 20 / ББК: 84(2Рос-Рус)-4